The Value of Adenosine Deaminase 2 in the Detection of Tuberculous Pleural Effusion: A Meta-Analysis and Systematic Review - Tingting Zeng; Bing Ling; Xueru Hu; Shuyan Wang; Wenliang Qiao; Lijuan Gao; Yongchun Shen; Dajiang Li (Canadian Respiratory Journal)
Adenosine deaminase 2 (ADA2) is reported as a novel diagnostic biomarker for tuberculous pleural effusion (TPE) in many studies. This meta-analysis was conducted to systematically evaluate the general diagnostic performance of pleural ADA2 in TPE. After searching for relevant studies that investigated the diagnostic performance of pleural ADA2 in TPE in several databases, we assessed and selected eligible studies to calculate pooled parameters by STATA 16.0 software. A final set of thirteen studies entirely met the inclusion standards and were used to calculate pooled parameters in our meta-analysis. Among them, there were nine English studies and four Chinese studies. The pooled parameters of pleural ADA2 in diagnosing TPE were summarized as follows: sensitivity, 0.91 (95% CI: 0.86–0.95); specificity, 0.93 (95% CI: 0.92–0.95); positive likelihood ratio, 13.9 (95% CI: 10.6–18.3); negative likelihood ratio, 0.09 (95% CI:0.06–0.16); diagnostic odds ratio, 147 (95% CI: 76–284); and the area under the curve, 0.95 (95% CI: 0.93–0.97). Pleural ADA2 is a reliable indicator with excellent accuracy in TPE diagnosis. However, we need to combine pleural ADA2 with diverse examinations to diagnose TPE in clinical practice.